RELIGIOUS MODERATION AND LIVING TOGETHER IN DIVERSITY: A HOLISTIC CONFUCIAN PERSPECTIVE (Jurnal Masyarakat dan Budaya, 2022)
As a matter of fact, religion is a complete and comprehensive teaching. Not only discussing the relationship between human being and the Creator, but also the relationship between human being and universe, fellow human, and the real of he/she him/herself. If a man/woman believes that religion only talks about Almighty God, or understands other relationships superficially, he/she can get stuck in the paradigm that the important thing is that he/she has prayed, worshiped Him, has been saved and does not care about other humans. Even more extreme when he/she thinks he/she is the best. This misunderstood is harmful. We truly know the Religious Moderation program was born because there are fears that fanaticism and blind extremism will monopolize the truth. This is of course early needs to be anticipated, especially since Indonesia is very diverse. Implementing this program without targeting all the main points of religious teachings - Divinity, the Natural Environment and everything in it, Humans and Humanity in relation to the Past, Future, Internal Environment, External Factor and the deepest part of the true human self, is not enough to guarantee optimal success. A holistic approach is needed that targets all aspects in a balanced way. This is what must be done in the right portion. Proper. Kongzi said, "What is lacking or excess is not enough. If the Middle Way and Harmony can be implemented, the world peace and prosperous is long lasting value”.